The Effectiveness of Using the Multi-Level ‎Self-Learning Strategy on Teaching Basic ‎Skills in Breaststroke Swimming among ‎Students of the Faculty of Sports Sciences, ‎Mu’tah University - Al-Tarawneh, Meqdad; Al-Ma'aitah, Lo'ai (Jordan Journal of Educational Sciences, 2024)
This study aimed to identify the effectiveness of using the strategy of multiple level self-learning in teaching basic skills in breaststroke. The researcher used the experimental approach. In order to achieve the study objectives, the study sample was purposefullychosen and consisted of 18 students. The sample was divided into two groups: an experimental group (n=9) students, who used the strategy of multiple level self-learning, and a control group (n=9) students who used the usual program. The two groups were tested in the pre and post measurements concerning a number of basic skills in breaststroke (sliding, leg strokes, arm motion, and total adjustment). The results revealed that there are statistically significant differences between the pre and post measurements for the tests of breaststroke among the individuals in the experimental group in favor of the post application. where they ranged between 0.47 and 0.471. The results revealed that there are statistically significant differences in the post -measurement tests of breaststroke between the control group and the experimental group in favor of the experimental group with a percentage that ranged between22.56% and 49.75%. These results indicated that there is a significant impact of the educational program on teaching the basic skills of breaststroke. In light of the results, the study recommended the necessity of using multi-level self-learning to promot the effectiveness of interaction between teachers and students as well as to overcome some problems related to individual differences between students in order to attain the best educational results